Combined associations of regular exercise and work-related moderate-to-vigorous physical activity with occupational stress responses: a cross-sectional study - Abe, Takafumi; Okuyama, Kenta; Motohiro, Atsushi; Shiratsuchi, Daijo; Isomura, Minoru (Frontiers in Sports and Active Living, 2024)
Objective The association between work-related moderate-to-vigorous physical activity (MVPA) and higher levels of stress response is recognized, but whether this association is moderated by regular exercise remains unclear. This cross-sectional study investigated whether exercise-based physical activity (PA) associates with lower levels of stress responses moderated by work-related MVPA. Methods The study participants comprised 863 workers from 35 small and medium-sized enterprises in Shimane prefecture, Japan, collected through convenient sampling from April 2021 to August 2022. The Brief Job Stress Questionnaire was used to assess stress responses. Work-related MVPA and exercise-based PA were measured using questionnaires. Multiple linear regression was used to analyze the combined variables of work-related MVPA and exercise-based PA. The reference group had no weekly exercise-based PA and >60 min of work-related MVPA. Results When work-related MVPA exceeded 60 min/day, flexibility activity or walking for ≥5 days/week (B = −3.53, 95% CI = −5.96, −1.11; B = −2.53, 95% CI = −4.90, −0.16) and muscle-strengthening activity 1–3 times/week (B = −3.52, 95% CI = −6.91, −0.12) were significantly associated with lower psychological stress response. Flexibility activity (B = −1.74, 95% CI = −3.01, −0.46) showed a similar link with physical stress response. When work-related MVPA was below 60 min/day, flexibility activity (B = −3.23, 95% CI = −6.01, −0.44; B = −3.29, 95% CI = −5.94, −0.63) or walking (B = −4.03, 95% CI = −6.62, −1.45; B = −3.10, 95% CI = −5.76, −0.44) practice 1–4 times/week and ≥5 times/week was significantly associated with lower psychological stress response. Conclusion Exercise-based PA greatly and consistently associates with a lower level of stress responses moderated by work-related MVPA.